Obtenção de Zeólitas sintéticas a partir de cinza volante ativada alcalinamente, tratada organicamente para uso como agente de adsorção de óleo e viscosificante. - Medeiros, Fabiana Kelly de (2015)
Zeolites are porous solids whose chemical composition is mainly formed of silicon and aluminum elements and silicon in the form of crystalline hydrated aluminosilicates. These materials have particular properties inherent its structural characteristics that make them useful in many industrial applications. The synthesis of zeolites from waste and natural sources of silicon and aluminum has stood out due to environmental and economic benefits. The raw material precursor used in this work is the fly ash from thermal power, whose conversion to zeolite is explained by its alkaline activation by sodium hydroxide (NaOH). This technique is characterized by low cost and because it is a technological alternative with great added value by transforming existing materials on a large scale in an innovative material. This study aims to obtain zeolites at low cost for subsequent treatment with organic surfactante, making it organoclays for use as adsorbent oil and viscosity agent for non-aqueous drilling fluids, the latter being an unprecedented application. The samples were characterized by sieve analysis techniques by Laser Diffraction (LALLS), X-Ray Diffraction (XRD), chemical composition by X-Ray Fluorescence (XRF), Differential Thermal Analysis (DTA) and Thermogravimetric (TGA) and Scanning Electron Microscopy (SEM). The evaluation of the adsorption capacity was carried out based on ASTM F716-12 and ASTM F726-12 standards and the analysis of viscosifying properties was based on the standard of Petrobras EP-1EP-00023A. As results we obtain the type of zeolites sodalite and cancrinita, from the transformation of fly ash, by synthesis, the concentration of 3.5 M, 5,25 M or 7,0 M NaOH for 24 h, 36 h or 48 h. It was verified the benefit of organophilization for the synthesized at 3.5 M NaOH samples. The determination of apparent viscosity, innovation in zeolites area, presents satisfactory results with attendance of standardized viscosity values.